The Secular Quest for Meaning Life: Dentom Papers in Implicit Religion (Book) - King, Christine (Implicit religion, 2003)
Reviews the book 'The Secular Quest for Meaning in Life: Denton Papers in Implicit Religion,' edited by Edward Bailey.